1982
DOI: 10.1148/radiology.143.1.7063727
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance imaging and evaluation of human breast tissue: preliminary clinical trials.

Abstract: In vivo clinical evaluations of human mammary tissue, including normal, dysplastic, and neoplastic breasts, were initiated using the FONAR method of nuclear magnetic resonance (NMR) imaging. Spin-lattice relaxation times (T1) were determined and correlated with other diagnostic modalities including mammography, xeroradiography, and sonography. Normal breasts and breasts with extensive fatty replacement were found to have the lowest T1 values, whereas T1 values of malignant tissue were elevated. T1 values for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 0 publications
0
20
0
6
Order By: Relevance
“…32 In previous studies, it was found that the accuracy of 1/T 10 propagated a significant, large error in the influx transcapillary transfer constant 32,33 ; the differences between benign lesions versus malignant lesions, however, were insignificant. 27,34,35 We found that the pattern of the progressive increase of k trans , from benign to IDC, persisted throughout all measured values of 1/T 10 (0.63-2.0 sec Ϫ1 ). Hence, the differences among the groups in both k trans and k ep reflect a genuine pathophysiologic phenomenon.…”
Section: Progressive Changes In the Vascular Parametersmentioning
confidence: 58%
“…32 In previous studies, it was found that the accuracy of 1/T 10 propagated a significant, large error in the influx transcapillary transfer constant 32,33 ; the differences between benign lesions versus malignant lesions, however, were insignificant. 27,34,35 We found that the pattern of the progressive increase of k trans , from benign to IDC, persisted throughout all measured values of 1/T 10 (0.63-2.0 sec Ϫ1 ). Hence, the differences among the groups in both k trans and k ep reflect a genuine pathophysiologic phenomenon.…”
Section: Progressive Changes In the Vascular Parametersmentioning
confidence: 58%
“…Because an early detection of the tumor is the primary strategy for reducing mortality (11, several methods such as mammography, sonography, and (recently) MRI have been developed. Different MRI techniques were investigated (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in the past in order to improve the detection and diagnosis of breast diseases. As a major result, these studies have shown that the sensitivity and specificity of MRI for the detection of breast cancer can be significantly increased by the use of paramagnetic contrast media (CM) such as gadolinium diethylenetriaminopentaacetic acid (Gd-DTPA) (4,5,10-Dynamic contrast-enhanced MRI studies were first performed by Kaiser and co-workers using rapid gradientecho imaging sequences (10).…”
Section: Introductionmentioning
confidence: 99%
“…A RM das mamas, no seu início na década de 80, utilizava-se apenas das imagens ponderadas em T1 e T2, havendo grande sobreposição de achados comuns às lesões benignas e malignas, o que desencorajou o seu uso [5,23] .…”
Section: Revisão Da Literaturaunclassified
“…A RM das mamas tenta desde então, aumentar a diferenciação entre lesões benignas e malignas [5,23] .…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation